The Economic Strategy to Deal With the Covid-19 Pandemic for Indonesia's Small and Medium-Sized People - Yulivan, Ivan (Dinasti Publisher, 2022)
Entering the middle of 2022, the Covid-19 outbreak is still ongoing, since the beginning of 2020 has impacted the economy of Indonesian communities, especially small and medium-sized communities.. Many businesses, especially Micro, Small and Medium Enterprises, went bankrupt and closed their businesses due to demand from consumers who fell free. This study uses the strategy theory of Lykke, 1989 which includes 3 (three) aspects of Ends, Ways and Means, with descriptive qualitative methods. various strategies. This paper aims to discuss the importance of the Government's Strategy in helping Micro, Small and Medium Enterprises during the COVID-19 pandemic in order to survive and continue to increase their business in supporting Indonesia's economic resilience. The results achieved are the need to improve strategies on Ways, including the right strategy starting with a regulatory framework and incentives in the form of policies in legislation, government regulations that are comprehensive and sustainable in helping the MSME sector to survive and get out of difficulties during the Covid pandemic. -19 so that it can support the economic resilience of the Indonesian people and nation.